Development of Ultra-Broadband Base Station Antenna for All Mainstream LTE 700/800/900 MHz Frequency Bands. (19th November 2014) - Samb, Doudou; Wu, Zhonglin; Liu, Mulin; Jie, Hu Bin
Abstract : LTE deployment is being accelerated due to its improved radio access structure meeting the requirements of current and next generation of wireless networks. Its low band application presents useful aspects such as low density of base station while providing good in-building penetration. In this work, we design and develop a dual-polarized base station antenna supporting 698 MHz to 960 MHz with an azimuth-plan half-power beam width of 90° covering all mainstream LTE 700/800/900 MHz frequency bands representing the widest low frequency range being actively used in the current mobile communication industry. In the design process, rigorous algorithm based on swarm method is developed to tune the electrical performances under strict base station antenna requirements. Experimental results from pattern tests demonstrate the design analysis and the significant advantages of using swarm method in the antenna development process.